Postmortem Change and its Effect on Evaluation of Fractures - Kemp, Walter L. (Acad Forensic Pathol, 2016)
Postmortem changes can both mask and mimic trauma, impairing interpretation of the injuries. Bones, while capable of surviving the postmortem period relatively intact, are not immune from these effects. Without attached soft tissue to aid an examiner, it can be difficult to determine the time frame of a fracture's occurrence (i.e., before death, at death, or after death). Bones are composed of both organic and inorganic material, each of which contribute to the biomechanical properties of the bones. With the loss of organic material, the biomechanical response of bones to trauma changes; however, the organic material can remain a part of the bone for an extended period after death. Bone with intact organic material is wet bone, and bone without the organic material is dry bone, and because of this difference, fractures of wet bone can appear different than fractures of dry bone. Important in distinguishing the two are differential coloration, various features of the fracture itself (e.g., angle, surface, outline), surrounding flaking of the cortex, and incomplete separation of bone fragments from the fracture. However, the changes are not absolute, and determination of the two types of fractures can be problematic. Although the terms antemortem, perimortem, and postmortem have been used to describe the general time frame of fractures in relation to the time of death of the individual, because of confusion among specialties regarding the definition of “perimortem,” its use may best be discontinued in favor of a descriptive approach when fractures are identified in skeletal remains.